Thermal performance evaluation of micro-fin tube with twisted tape inserts - Eiamsa-Ard, Smith; Kunlabud, Suttisak; Wongcharee, Khwanchit; Pimsarn, Monsak; Eiamsa-Ard, Petpices (My University, 2015)
The heat transfer coefficient and pressure drop characteristics of turbulent flow through micro-fin tubes fitted with twisted tape in co/counter-arrangement have been studied. In the experiments, water as the tested fluid is passed in a Reynolds number range of 7800 to 17,650. The results reveal that, the Nusselt numbers in the system with a micro-fin tube and twisted tape are considerably higher than those in the system without tape. Evidently, the tape with the smaller twist ratio gives higher heat transfer rate, friction factor as well as thermal performance factor than the one with larger twist ratio as a result of a larger contact surface area, and stronger turbulence intensity and thus better fluid mixing which leads to a thinner thermal boundary layer. The result reveals that for using the micro-fin tube with twisted tape, the increases in the mean Nusselt number and friction factor are, respectively, up to 181% and 3.86 times of the plain tube and the maximum thermal performance factor is 1.52. It is also obvious that the heat transfer and friction factor obtained from the micro-fin tube with twisted tape in counter-arrangement is higher than that from the micro-fin tube with twisted tape in co-arrangement.
Keywords: Co-arrangement(CoT); Counter-arrangement(CT); Heat transfer enhancement; Micro-fin tube (MT); Swirl flow; Twisted tape